2018
DOI: 10.1891/0889-8391.32.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and Mindlessness Processes: Trajectories of Change in a 42-Day Mindfulness-Based Intervention

Abstract: This preliminary study aimed to understand the effects of an autonomous mindfulness-based intervention (MBI) on mindlessness propensities: rumination, automatic pilot functioning, and attentional distractibility. The ecological momentary assessment was completed by community participants assigned to two nonrandomized groups: an experimental group (n = 45) that practiced 20-minute daily mindfulness meditation for 42 days and a control group (n = 44) that was on the waiting list for the MBI. All participants com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 47 publications
(100 reference statements)
0
12
2
1
Order By: Relevance
“…Shapiro trained 83 college students in mindfulness-based stress reduction (MBSR) to reduce successfully the degree of rumination (15). While monitoring the 42-day mindfulnessbased intervention (MBI) process of 45 participants, Andreotti found that the degree of rumination decreased significantly after 1 week and 1 month (16). Mindfulness cultivates nonjudgmental, nonreactive attention to the present moment; however, it can also be experienced in other ways, except for professional mindfulness training (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Shapiro trained 83 college students in mindfulness-based stress reduction (MBSR) to reduce successfully the degree of rumination (15). While monitoring the 42-day mindfulnessbased intervention (MBI) process of 45 participants, Andreotti found that the degree of rumination decreased significantly after 1 week and 1 month (16). Mindfulness cultivates nonjudgmental, nonreactive attention to the present moment; however, it can also be experienced in other ways, except for professional mindfulness training (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In line with Hypothesis 2, the overall evaluation of meditation success improved as well: the participants who kept engaging with the intervention felt that they were gradually mastering meditation. Based on the existing findings and theory (Andreotti et al, 2018; Rosenkranz et al, 2019), we explored whether the change trajectories were linear. Meaning emerged as the only DV with a curvilinear trajectory showing a faster increase during the initial week, which may reflect emergent motivation to practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have used intensive longitudinal data to explore individual differences in the trajectories of change in affect, stress, and mindfulness outcomes during mindfulness training (Andreotti et al, 2018; Kiken et al, 2015; Snippe et al, 2015; Snippe et al, 2017). In the two studies linking these trajectories to other variables, the individual slopes reflecting changes in state mindfulness predicted the subsequent changes in trait mindfulness, psychological distress, and affect, but were not associated with baseline mindfulness, affect, and distress levels (Kiken et al, 2015; Snippe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The heightened self-consciousness [85,86] and concern about social evaluation [87] that are characteristic of early adolescence may particularly implicate rumination during this developmental period. In addition, given that mindfulness interventions reduce rumination [88][89][90], future research should examine the efficacy of mindfulness training in disrupting this potentially pernicious process. Future research should also consider the possibility that the link from victimization to mindfulness flows in the opposite direction.…”
Section: Plos Onementioning
confidence: 99%